Analysis of Students' Scientific Literacy Dimensions in Citizen Science Projects - Harto Nuroso; Ernawati Saptaningrum; Ummi Kaltsum; Wawan Kurniawan; Joko Siswanto (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2026)
The low scientific literacy of Indonesian students, consistently below the international average, according to the PISA survey, demands contextual and participatory learning innovations. This study aims to analyze the dimensions of scientific literacy in high school students through the implementation of a citizen science project on the topic of mechanical energy, evaluating its effectiveness as a pedagogical strategy to address the persistently low science literacy of Indonesian students. The research uses a mixed-methods approach, focusing on analyzing the use of mechanical energy in students' daily transportation. The results show a significant improvement in students' understanding of physics concepts, particularly in the context dimension (the ability to apply knowledge to real situations) and the attitude dimension (interest in science). However, the study also identifies an area requiring further development: the science process dimension, specifically the skills to critically evaluate data and scientific processes. In conclusion, citizen science successfully transformed learning from theoretical memorization into a meaningful, authentic inquiry experience. For sustainability and optimization, a systemic commitment is needed to integrate this approach into the curriculum, along with adequate training and resource support for teachers, to equip students with the science competencies required for the 21st century.